Strategic Decision-Making in The Development Scenario Selection for The Kayu Merah Structure at Jatibarang Field, PT Pertamina EP - Hermawan Hermawan; Pri Hermawan (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aims to support strategic decision-making in determining the most optimal development scenario for the KYM gas structure through an integrated analytical approach. The research identifies internal and external factors influencing development feasibility, translates stakeholder values into decision criteria, and systematically evaluates alternative scenarios. The method combined qualitative and quantitative approaches through PESTEL analysis, SWOT analysis, Value-Focused Thinking (VFT), and the Analytic Hierarchy Process (AHP). Primary data were obtained through surveys, semi-structured interviews, focus group discussions, and stakeholder mapping, while secondary data were derived from internal company documents, regulations, technical studies, and academic literature. The results of the environmental analysis were used to formulate fundamental objectives, means objectives, criteria, and sub-criteria for evaluation that align with strategic priorities and stakeholder expectations. The alternative development scenarios were then evaluated using AHP pairwise comparisons, accompanied by consistency ratio testing and sensitivity analysis. The findings indicate that Alternative 1, namely the production flow from KYM-B and KYM-C wells through the construction of a new flowline integrated with existing production toward the Randegan Gathering Station with facility upgrades, is the most optimal scenario. This alternative is superior because it provides a balanced performance across economic, technical-operational, regulatory-environmental, implementation risk, and stakeholder alignment aspects. The sensitivity analysis shows that the selected alternative remains robust against changes in criteria weights, with the project approval target in the second quarter of 2026 and onstream target in the fourth quarter of 2028.